PERAN KREDIT PERBANKAN PADA SEKTOR PERTANIAN DI PROVINSI SULAWESI UTARA - Desyani ., Panekenan; Grace A. J. Rumagit; Paulus A. Pangemanan (Sam Ratulangi University, 2017)
The study aims to determine how the role of bank credit in 2011 through 2016 in the agricultural sector in the province of North Sulawesi. The study was conducted in November 2016 until January 2017. The data used is descriptive data of quantitative and qualitative data sources are primary data and secondary data obtained from the events on the ground or opinion of a subject field related to the provision of credit to the agricultural sector, and resources that are not directly provide data to investigators, obtained by way of written documentation regarding matters necessary or variable of Bank Indonesia Representative of North Sulawesi. Analysis of the data used is descriptive analysis method of data analysis of quantitative and qualitative concerning the description of bank credit to the agricultural sector in the province of North Sulawesi. Analysis of data taken, namely Bank Indonesia report the amount of credit to the agricultural sector of the Year 2011 to the 2016. These descriptive data analysis aims to find bank financing in the agricultural sector in the province of North Sulawesi, which will be presented in the form of tables and graphs as well as to see the development lending. The results showed that the role of bank credit to the agricultural sector in the province of North Sulawesi is increasing every tahunnya dari in 2011 through 2016 with an average growth 14.36%. With the increase in the agricultural sector credit each year, meaning that the banks increasingly trusted by the community to help strengthen the capital of agricultural business operators in this regard in the form of lending.